(3EJbGf GdUfYI aj GdJLhjO ddSHYIs - (3GHf TYjH , CMeO Hf TYjH GdCfOdSj GdaGSj,J (B1015 (3g` s
(3ChdgG (B:s
(3hHYO ef GdJcaj GdSOjO hGdQCi GdQTjO Cf CVY gPG s
(3BNQgG (B:s
(3hdef OYG dg HGdeZaQI hdLejY GdeSdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B135 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B244s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B22s
Keywords: (3GdbQGAGJ hGdJLhjOs